What Does Time-Dependent Fluorescence Shift (TDFS) in Biomembranes (and Proteins) Report on? - Scollo, Federica; Evci, Hüseyin; Amaro, Mariana; Jurkiewicz, Piotr; Sykora, Jan; Hof, Martin (Frontiers in Chemistry, 2021)
The organization of biomolecules and bioassemblies is highly governed by the nature and extent of their interactions with water. These interactions are of high intricacy and a broad range of methods based on various principles have been introduced to characterize them. As these methods view the hydration phenomena differently (e.g., in terms of time and length scales), a detailed insight in each particular technique is to promote the overall understanding of the stunning “hydration world.” In this prospective mini-review we therefore critically examine time-dependent fluorescence shift (TDFS)—an experimental method with a high potential for studying the hydration in the biological systems. We demonstrate that TDFS is very useful especially for phospholipid bilayers for mapping the interfacial region formed by the hydrated lipid headgroups. TDFS, when properly applied, reports on the degree of hydration and mobility of the hydrated phospholipid segments in the close vicinity of the fluorophore embedded in the bilayer. Here, the interpretation of the recorded TDFS parameters are thoroughly discussed, also in the context of the findings obtained by other experimental techniques addressing the hydration phenomena (e.g., molecular dynamics simulations, NMR spectroscopy, scattering techniques, etc.). The differences in the interpretations of TDFS outputs between phospholipid biomembranes and proteins are also addressed. Additionally, prerequisites for the successful TDFS application are presented (i.e., the proper choice of fluorescence dye for TDFS studies, and TDFS instrumentation). Finally, the effects of ions and oxidized phospholipids on the bilayer organization and headgroup packing viewed from TDFS perspective are presented as application examples.